Implementação e análise de sistema de produção de energia elétrica em propriedade rural com módulos fotovoltaicos de silício multicristalino - Araujo, Nadine Demacena de (2019)
The electric energy produced with photovoltaic systems represents 0.1 % of the national energy matrix, summing an installed power of more than 1.5 GW. The objective of this work is to present the development and analysis of a photovoltaic system of 20 kWp installed in a rural property in the western Paraná using photovoltaic modules with solar cells of multicrystalline silicon, through software simulation, evaluation of the electrical characteristics of photovoltaic modules, evaluation of the effective temperature of the modules, analysis of the merit parameters and calculation of the payback. The system was designed and its operation was simulated with the PV * SOL program, obtaining the optimum tilt angle 18 ° for the array, estimated yield of 1452 kWh / kWp and performance ratio of 86.3 %. The photovoltaic modules were electrically characterized under standard conditions and the mean value was (278.9 ± 0.9) W, all of which presented power above the catalog value. The mean effective temperature of the photovoltaic modules calculated with experimental values was lower than that obtained in the simulation, but the equivalent temperature estimation showed that it is crucial to use wind speed in calculations. In eight months of operation of the photovoltaic system, the average productivity was 7 % lower than that estimated in the simulation, but a performance ratio in average 3 % higher than that of the simulation, with the average performance ratio of 89 %. This result is an indicative of a successful installation. Regarding the payback time of the installed photovoltaic system, a period of 7.8 years was estimated, a payback greater than that of urban areas due to the lower value of kWh in rural areas.